2021
DOI: 10.1371/journal.pone.0249012
|View full text |Cite
|
Sign up to set email alerts
|

State-level prevalence estimates of latent tuberculosis infection in the United States by medical risk factors, demographic characteristics and nativity

Abstract: Introduction Preventing tuberculosis (TB) disease requires treatment of latent TB infection (LTBI) as well as prevention of person-to-person transmission. We estimated the LTBI prevalence for the entire United States and for each state by medical risk factors, age, and race/ethnicity, both in the total population and stratified by nativity. Methods We created a mathematical model using all incident TB disease cases during 2013–2017 reported to the National Tuberculosis Surveillance System that were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…The LTBI rate in this study was unexpectedly higher than the reported rate in the United States (i.e., 2.7%), 33 which can be attributed to the high rate of foreign‐born individuals from TB‐endemic areas (16%) in our cohort. Our study highlights the importance of LTBI screening based on risk factors for TB 34 .…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The LTBI rate in this study was unexpectedly higher than the reported rate in the United States (i.e., 2.7%), 33 which can be attributed to the high rate of foreign‐born individuals from TB‐endemic areas (16%) in our cohort. Our study highlights the importance of LTBI screening based on risk factors for TB 34 .…”
Section: Discussioncontrasting
confidence: 76%
“…Other factors associated with indeterminate IGRA results that we did not explore, include medical comorbidities, including hepatitis C, and low lymphocyte counts. 24,30 The LTBI rate in this study was unexpectedly higher than the reported rate in the United States (i.e., 2.7%), 33 which can be attributed to the high rate of foreign-born individuals from TB-endemic areas (16%) in our cohort. Our study highlights the importance of LTBI screening based on risk factors for TB.…”
Section: Discussionmentioning
confidence: 48%
“…The prevalence of LTBI may vary based on age group and ethnicity. In a study performed in US, the highest prevalence of LTBI was noted in persons ≥ 65 years among US-born persons and in persons between the ages of 45 and 64 years among non-US-born persons 11 .…”
Section: Epidemiology Of Ltbi In the General Populationmentioning
confidence: 96%
“…The LTBI prevalence is very high in countries such as Haiti, Peru, Ethiopia, Somalia, Buthan and Vietnam (range: 42% to 55%) 10 . The estimated prevalence of LTBI in US is only 2.7% 11 . The prevalence of LTBI may vary based on age group and ethnicity.…”
Section: Epidemiology Of Ltbi In the General Populationmentioning
confidence: 99%
“…This was due to several challenges including multidrug-resistant (MDR)-TB and sub-optimal clinical and public health management of the condition in certain countries. In 2019, about 2.7 cases of TB were reported per 100,000 people [ 3 ].…”
Section: Introductionmentioning
confidence: 99%